A Unified Theory of Underreaction, Momentum Trading, and Overreaction in Asset Markets - Hong, Harrison; Stein, Jeremy C. (Journal of Finance, 1999)
ABSTRACT We model a market populated by two groups of boundedly rational agents: “newswatchers” and “momentum traders.” Each newswatcher observes some private information, but fails to extract other newswatchers' information from prices. If information diffuses gradually across the population, prices underreact in the short run. The underreaction means that the momentum traders can profit by trend‐chasing. However, if they can only implement simple (i.e., univariate) strategies, their attempts at arbitrage must inevitably lead to overreaction at long horizons. In addition to providing a unified account of under‐ and overreactions, the model generates several other distinctive implications.